E, Efek EFEKTIVITAS PELATIHAN PEMBUATAN NUGGIPRO PADA MASYARAKAT NELAYAN GISIK CEMANDI SIDOARJO JATIM - Isnawati Isnawati; Mahanani Tri Asri; Lisa Lisdiana; Fitriari Izzatunnisa Muhaimin (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2023)
Nuggets are a food that is especially liked by children. Nuggets are used as a side dish or as a snack while relaxing. Based on this, it is very necessary to develop nuggets that are healthier and more delicious. The aim of the PKM activity is to help partners solve their problems related to the management of unsold caught fish and to explain the effectiveness of training on making fish-based nuggets containing probiotics called NuggiPro which has the potential as an innovative entrepreneurial activity in the Gisik Cemandi fishing community, Sidoarjo East Java, as a solution to partner problems. The methods used in this training include (1) gathering participant knowledge information related to the aspects being trained (2) playing a video on the manufacture of NuggiPro, (3) providing information (3) demonstration of the manufacture of NuggiPro by the team, (4) practice of making NuggiPro by the training participants and (5) evaluation of results. The results of this PKM activity include that (1) partners' initial knowledge regarding processing unsold caught fish is still low (2) knowledge and skills in making NuggiPro as a solution to managing unsold fish is still low (3) after knowledge training and the NuggiPro manufacturing skills increased (4) the NuggiPro made by the trainees fulfilled the SOP (5) the participants gave a positive response to the NuggiPro manufacturing training and its potential as an entrepreneurial activity. Based on the results achieved, it can be stated that the PKM activity was successful.